(Re)Interpretasi Menolong Agama Allah: Penafsiran QS. Muhammad [47]: 7 dan QS. al-Hajj [22]: 40 - Izza Royyani; Azizah Kumalasari (NALAR, 2020)
This article departs from the reality that textualism is still found in the discourse of defending God's religion, especially in classical interpretations of the Quran. Such an interpretation becomes a polemic indeed when we read it today. Al-Tabari, for example, interprets the discourse textually that to defend Allah means al-jihad fi sabilillah and therefore He will help. This article tries to reconsider the understanding of defending the religion of Allah in the surah Al-Hajj [22]: 40 and surah Muhammad [47]: 7. It uses the ma'na cum maghza method initiated by Sahiron Syamsudin. It tries to interpret the verses by tracing the literal understanding of the texts by reviewing them both linguistically and contextually. Afterwards it looks for the significance or the main message of the verses (maghza) which can be applied in this modern era. So, it is hoped that a contextual interpretation of the two verses will be born. This research concludes that what is meant by helping the religion of Allah is about conveying the truth, purifying Islam within Muslims themselves, respecting religious pluralism, understanding today's ameaning of the enemy of Islam  and the essence of jihad, one of which is inclusive thinking.Keywords: Reinterpretation, Ma'na cum Maghza, Helping Religion